Anglo-French Negotiations Concerning Cameroon during World War I, 1914-1916: Occupation, "Condominium" and Partition - Lovett Z. Elango (Journal of Global Initiatives, 2015)
Anglo-French disagreements over Cameroon during World War I and the efforts to resolve them both during the Allied campaigns in the territory and at the end of the war suggest that negotiation can occur even in wartime successfully. At the outbreak of the war Cameroon was a German territory like Tanganyika, South West Africa, and Togoland. The Anglo-French grand strategy and war aims were to seize these territories and oust the Germans from them. Consequently, Cameroon became the theater of an intense military struggle and a pawn of Anglo-French imperial rivalry fuelled by the conflicting territorial ambitions and claims of France and Britain. The outcome was that both countries, after protracted and often acrimonious negotiations over pieces of territory that were typical of 19th-century imperialism, eventually abandoned a proposed condominium for the joint administration of Cameroon in favor of outright partition of the territory although Cameroonians were absent from the negotiations. This paper highlights the issues and traces the main stages in the evolving disagreement that led to this outcome. It is based on research conducted at the Public Record Office (PRO), now National Archives, London. I am grateful to the British Council for its generous bursary, which made it possible.